2014
DOI: 10.2967/jnumed.114.141861
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Labeling Strategy for In Vivo PET and Near-Infrared Fluorescence Imaging of Nanoparticle Tumor Targeting

Abstract: Advances in preclinical molecular imaging have generated new opportunities to noninvasively visualize the biodistribution and tumor targeting of nanoparticle therapeutics. Capitalizing on recent achievements in this area, we sought to develop an 89Zr-based labeling strategy for liposomal nanoparticles that accumulate in tumors via passive targeting mechanisms. Methods 89Zr-labeled liposomes were prepared using 2 different approaches: click labeling and surface chelation. Pharmacokinetic and biodistribution st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 38 publications
0
95
0
Order By: Relevance
“…Similar bone uptake values have been found with long-circulating (>24 h) 89 Zr-labeled antibodies and liposomes, suggesting that these bone-targeting species are nonchelated 89 Zr released after liposome disassembly. 19,4143 Highly vascular organs such as the lungs and kidneys followed the same decreasing trend in signal as the heart/blood, as expected for long-circulating nanoparticles that are cleared via the reticuloendothelial system (RES). One animal from the group was further imaged at 168 h to confirm the biodistribution trend.…”
Section: Resultsmentioning
confidence: 71%
“…Similar bone uptake values have been found with long-circulating (>24 h) 89 Zr-labeled antibodies and liposomes, suggesting that these bone-targeting species are nonchelated 89 Zr released after liposome disassembly. 19,4143 Highly vascular organs such as the lungs and kidneys followed the same decreasing trend in signal as the heart/blood, as expected for long-circulating nanoparticles that are cleared via the reticuloendothelial system (RES). One animal from the group was further imaged at 168 h to confirm the biodistribution trend.…”
Section: Resultsmentioning
confidence: 71%
“…The first one was synthesized by conjugation of DFO to apoA-I via reaction of the rHDL particles with DFO- p -NCS. The second one, the phospholipid-based chelator DSPE-DFO, was prepared as recently described by us (21). These modifications had no measurable effect on the size, compared with plain rHDL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Pérez-Medina et al employed a copper-free click reaction to label 89 Zr with a DFO azide and then couple the corresponding 89 Zr-DFO azide to the lipid-bonded dibenzocyclooctynyl group on the liposome surface. 10 Low isolated RCY of 14% was observed in this two-step method with a prolonged preparation time of 16 h. As an alternative to the lipid membrane-labeling strategy, the radioisotopes can also be localized in the liposomal cavity. In 2011, Petersen et al reported a remote loading approach to label liposomes with 64 Cu.…”
Section: Introductionmentioning
confidence: 99%